Review of Marcus Mescher, The Ethics of Encounter: Christian Neighbor Love as a Practice of Solidarity - Jessica Wrobleski (Journal of Moral Theology)
Review of Marcus Mescher, _The Ethics of Encounter: Christian Neighbor Love as a Practice of Solidarity_